Leveraging friendshoring in response to sanctions: Essential insights for global managers - Klarin, Anton; Sosnovskikh, S. (Elsevier, 2024)
As the world has become increasingly hostile and politicized, sanctions have become an often-used tool for enforcing global rules. Nevertheless, organizations engaged in international trade have found ways to circumvent imposed sanctions and to deliver goods and services to the sanctioned markets through a variety of means, including offshoring, nearshoring, and, most importantly, friendshoring. There has been a notable increase in these shoring phenomena, especially in the context of global disruptions, including the COVID-19 pandemic, the United States and China trade conflicts, and sanctions related to the Russia–Ukraine War. This study offers a rich account of how organizations overcome economic sanctions that lead to restrictions in trade among trading partners. After holding in-depth interviews with representatives from 44 organizations involved in trade in nine imposing, intermediary, and targeted countries, we synthesized six main friendshoring strategies often used in instances where sanctions are imposed. We end by offering prescriptive guidance for managers whose companies face difficult shoring decisions because of sanctions.